Vitamin D: role of vitamin D in human health beyond skeleton - Singh, Ambrish; Soni, Ameet; Changani, Mohit; Choksi, Harsh (International Journal of Advances in Medicine, 2020)
Deficiency of vitamin D is now considered as epidemic in Indian subcontinent, with a prevalence of 70-94% in the general population. Like in US, Indian dairy products are rarely fortified with vitamin D. Socioreligious and cultural practices followed in India do not facilitate adequate sun exposure, thereby negating potential benefits of plentiful sunshine resulting in vitamin D deficiency. Deficiency is highly prevalent in both urban and rural settings. Vitamin D deficiency can lead to rickets, osteoporosis, cardiovascular diseases, diabetes, cancer and infections. In present review authors have revisited the details pertaining to vitamin D to increase the awareness on Vitamin D efficiency.